O impacto da inovação empresarial na performance financeira: o caso das PME excelência portuguesas - Silva, Diana Maria Marques da (2021)
Innovation is considered a fundamental factor for the growth and competitiveness of companies, allowing them to differentiate themselves from competitors and build competitive advantages in an increasingly complex and global market. However, the literature is still quite inconclusive regarding the impact of innovation on corporate performance. This study is directed to the “SMEs Excellence” of the Portuguese Manufacturing Industry. The status of “SMEs Excellence” is granted by a national state agency that supports SMEs, called IAPMEI. The main objective of this work was to analyze the impact of innovation on the financial performance of SMEs Excellence in the period between 2011 and 2019. Additionally, it was analyzed whether this impact is more pronounced in SMEs Excellence than in other SMEs. The intensity of intangible assets was used as a proxy for innovation, obtained through the ratio between total intangible assets and total company assets. To analyze the financial performance, the return on assets and the return on equity were used. The data were collected from the SABI and IAPMEI databases. The study analyzed 5427 companies (SMEs Excellence and SMEs Non-Excellence) belonging to the Portuguese Manufacturing Industry, in the period between 2011 and 2019. The results were obtained using the fixed effects panel data methodology. The main results suggest that innovation has a positive and significant impact on the financial performance of SMEs Excellence, however, considering all SMEs, the result is the opposite. Additionally, the results revealed that this impact is greater in exporting companies.